With or without you – pair fidelity and divorce in monogamous birds - Culina, A (2014)
The drivers of fidelity and divorce of pair-bonded individuals, along with their fitness consequences, are of great interest as they influence mating systems, population structure and productivity, and gene flow. Socially monogamous birds offer an ideal opportunity to study divorce since they show great variability in the extent to which pair bonds are maintained. However, there has been little consensus as to whether divorce is a behavioural adaptation to improve a mating situation, or a consequence of other processes. Moreover, the biological and ecological correlates of fidelity are difficult to address because previous work has been based on indirect and potentially biased methods. Finally, in terms of process, the link between the process of mate choice and subsequent mating decisions has been largely inaccessible to study. My doctoral thesis addressed these significant gaps in our understanding of cause, process and consequence in the formation and dissolution of pair bonds in socially monogamous birds. I accomplished this in three principal ways. First, I conducted a robust phylogenetic meta-analysis on 84 studies across 64 species to assess the existing empirical evidence that divorce in socially monogamous birds is adaptive (in terms of breeding success). This analysis revealed that divorce is, in general, adaptive as it is both triggered by relatively low breeding success and leads to improvement in success. Next, I developed a novel probabilistic multievent capture–mark–recapture framework that provides joint estimates of survival and fidelity while explicitly accounting for imperfect detection, capture heterogeneity, and uncertainty in pair status. By applying this model to breeding data on a wild great tit population I showed that birds that remain faithful to their partner exhibit higher survival rates and are more likely to remain faithful in the next breeding season than do birds that change partners. Subsequently, I confirmed the generality of a survival benefit by applying the model to breeding data on other tit populations. Then, by applying the model to data from a population of mute swans, I showed that fidelity decreases the likelihood of skipping breeding and mortality in this long-lived species, and that these effects depended on age, individual quality, and immigration status. Finally, I investigated how the timing of pair formation influences breeding success and divorce probability using five years of data on the over-winter social behaviour of great tits. I showed that early pair formation had a positive effect on fitness components, influencing the likelihood of divorce only indirectly, through breeding success. Further, my work revealed that males, but not females, with higher numbers of the female associates in winter, and males whose future breeding partners were ranked low amongst these, divorced more often. My research makes a significant contribution to our understanding of divorce and fidelity, and generates a number of important implications for future studies. First, my work establishes that divorce is adaptive for breeding success. Second, my results highlight that survival is an important (and likely, widespread) fitness consequence of pairing decisions. Third, I provide a novel statistically rigorous modelling framework for estimating fidelity-rates and testing hypothesis about fidelity that overcomes many of the inherent biases in traditional estimates. Fourth, it provides the first evidence for a selective advantage of early pair formation in wild, thus highlighting that there are benefits to pair familiarity that manifest via social associations of individuals prior to breeding. Finally, my work reveals the selective pressures operating via the social environment can ultimately influence the mating strategies individuals adopt.